On the Kinetics of Loess Disintegration - Li, Xi-An; Yan, Yong-Li (Asian Journal of Chemistry, 2011)
The disintegration kinetics of loess was investigated in presence of various initial water contents. The disintegration rates were determined by reading the volume of the disintegration as a function of time. Effect of the water content on the kinetic stability of loess was also discussed. The disintegration behaviour was well fitted by the empirical equation Wt = Wmaxtn/(Kn + tn). Three distinct stages of loess disintegration behaviour determined by independent mechanisms were identified from analysis of the rate of loess disintegration as a function of time. The mechanism of influence on the disintegration made by initial water ratio is analyzed.